Genome-wide identification of terpenoid synthase family genes in Gossypium hirsutum and functional dissection of its subfamily cadinene synthase A in gossypol synthesis - Wen, Tianyang; Xu, Xiao; Ren, Aiping; Zhao, Ge; Wu, Jiahe (Frontiers in Plant Science, 2023)
Plant terpenoid synthase (TPS) family genes participate in metabolite synthesis, hormones, gossypol, etc. Here, we genome-widely identified TPS family genes in 12 land plant species. Four hundred and thirty TPS-related genes were divided into seven subfamilies. The TPS-c in Bryophytes was suggested to be the earliest subfamily, followed by the TPS-e/f and TPS-h presence in ferns. TPS-a, the largest number of genes, was derived from monocotyledonous and dicotyledonous plants. Collinearity analysis showed that 38 out of the 76 TPS genes in G. hirsutum were collinear within G. arboreum and G. raimondii. Twenty-one GhTPS-a genes belong to the cadinene synthase (GhCDN) subfamily and were divided into five groups, A, B, C, D, and E. The special cis-elements in the promoters of 12 GhCDN-A genes suggested that the JA and ethylene signaling pathways may be involved in their expression regulation. When 12 GhCDN-A genes were simultaneously silenced through virus-induced gene silencing, the glandular color of GhCDN-A-silenced plants was lighter than that of the control, supported by a gossypol content decrease based on HPLC testing, suggesting that GhCDN-A subgroup genes participate in gossypol synthesis. According to RNA-seq analysis, gossypol synthesis-related genes and disease-resistant genes in the glandular variety exhibited upregulated expression compared to the glandless variety, whereas hormone signaling-related genes were downregulated. All in all, these results revealed plant TPS gene evolution rules and dissected the TPS subfamily, GhCDN-A, function in gossypol synthesis in cotton.